الالتزام القانوني لصاحب العمل بتنظيم وقت العمل دراسة في قانون العمل السوداني - الجيلاني حسين, علي حسين (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 1 (2023), 2026)
التزام صاحب العمل بتنظيم وقت العمل وتحديد أوقات الراحة يُعد من الأمور الضرورية التي يحتاجها طرفا العلاقة التعاقدية في عقد العمل وتؤثر بصورة كبيرة في العمل داخل المنشأة، حيث يحتاج العامل إلى أوقات للراحة خلال ساعات العمل اليومية حتى يتمكن من أداء عمله بصورة طبيعية تتماشى مع مقدرته الجسدية والعقلية، كما يحتاج إضافة إلى ذلك لأوقات أخرى يتوقف فيها عن العمل لأسباب أخرى متنوعة كأن تُعطى له إجازات مدفوعة الأجر حتى يستعيد نشاطه البدني والنفسي ويقوم بأداء واجباته الاجتماعية داخل مجتمعه. تأتي أهمية الدراسة من أن هناك حاجة ملحة لخلق توازن بين مصلحة طرفي عقد العمل في مدى الوقت الذي يقوم فيه العامل بالعمل والوقت الذي يمكن صاحب العمل من تحقيق الإنتاجية المرجوة من عمله، هدفت هذه الدراسة إلى بيان التزام صاحب العمل بتنظيم أوقات العمل اليومية وأساس هذا الالتزام، وتوضيح الأحكام المتعلقة بساعات العمل والإجازات. اتبعت الدراسة المنهج الوصفي والاستقرائي التحليلي والمقارن، وتوصّلت إلى عدة نتائج أهمها أن التزام صاحب العمل يستوجب وضع لائحة لذلك فيها مصلحة ظاهرة للعمال لأنّها تجعلهم على بينة من شروط عملهم، فيقومون بما هو مفروض عليهم من واجبات، ويطالبون بما هو مقرر لهم من حقوق، وأن سلطة صاحب العمل في إصدار لائحة النظام الأساس هي سلطة كفلتها له التشريعات لينظم بها العمل- لا سيما أوقاته- وتُعد التزاماً عليه، إلا أنّها ليست سلطة مطلقة، إذ تتقيّد من ناحية باحترام شروط العقد والقوانين الآمرة والقواعد المتعلقة بالنظام العام والآداب. أوصت الدراسة بعدة توصيات أهمها ضرورة التوازن بين المصالح المتعارضة لكل من طرفي عقد العمل من جانب والمشرع من جانب، للوصول إلى أقل أوقات العمل للعامل وتحقيق أكبر فائدة لصاحب العمل.      The employer’s commitment to organizing work time and determining rest times is one of the necessary matters that both parties to the contractual relationship need in the employment contract and it greatly affects the work within the facility, as the worker needs times to rest during the daily working hours so that he can perform his work in a natural way that is consistent with his physical capabilities. He also needs to add to that other times when he stops working for various other reasons and is given paid leave until he regains his physical and psychological activity and performs his social duties within his community. The importance of the study comes from the fact that there is an urgent need to create a balance between the interests of both parties to the employment contract in terms of the time during which the worker does the work and the time that enables the employer to achieve the desired productivity from his work. This study aimed to clarify the employer's obligation to regulate daily working hours and the basis for this obligation, and to clarify the provisions related to working hours and vacations. This study followed the descriptive and inductive analytical and comparative approach, and reached several results, the most important of which is that the employer’s obligation to organize work and to establish regulations for that is in the apparent interest of the workers because it makes them aware of the conditions of their work, so they carry out the duties imposed on them and demand what is decided for them. Rights, and that the employer’s authority to issue statute regulations is a power guaranteed to him by legislation to regulate work - especially its time - and is considered an obligation on him. However, it is not an absolute authority, as it is bound, on the one hand, by respecting the terms of the contract, peremptory laws, and rules related to public order and morals. The study recommended several recommendations, the most important of which is the need for a balance between the conflicting interests of both parties to the employment contract on the part of the legislator, in order to achieve the shortest working hours for the worker and achieve the greatest benefit for the employer.